A review of researches about human thermal comfort in semi-outdoor spaces - Goshayeshi, Danial; Shahidan, Mohd Fairuz; Khafi, Farzaneh; Ehtesham, Ezzat (Gamut s.r.o., 2013)
The role of human thermal comfort on sustainable architecture and urban design is substantial. To concentrate on outdoor thermal comfort subject as well as indoor thermal comfort is a key to solve the global warming andwasting energy problems for future years. Semi-opened spaces as favorable and frequent spaces for people in urban areas affect strongly the quality of life and well-being of persons. Although the assessments of outdoor thermal comfort have been increased in recent years, the number of researches that primarily focused on human thermal comfort in semi-outdoor spaces is few. This article reviews the studies about semi-opened spaces have been executed in various climate conditions since late years. Furthermore, it explained the general assessment methods of the semi-outdoor thermal comfort.